Самосогласованные поля живой материи - Симонов, И.Н.; Трофимович, В.В. (Екологічна безпека та природокористування, 2012)
This paper analyzes the experimental and theoretical background of possible existence fields of living matter. Our analysis suggests that the electromagnetic field of living the matter is associated with self-consistent fields of aqueous solutions of electrolytes, which are present in almost all parts of living tissue. Nonequilibrium radiation of biological objects are determined by changes in the equilibrium values of the concentrations of ions, which is accompanied by transition of ions from a state with one interaction energy in a state with other the energy.